2019
DOI: 10.1186/s12885-019-5711-4
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of distant metastasis in parotid acinic cell carcinoma

Abstract: Background Distant metastasis (DM) is a common treatment failure pattern in acinic cell carcinoma (AciCC) of the major salivary glands; therefore, the main goal of this study was to analyse the predictors of DM in parotid AciCC. Methods Consecutive patients with surgically treated parotid AciCC who were followed for at least 5 years were retrospectively reviewed. Data regarding age, sex, TNM stage, pathologic characteristics, surgical treatment, and follow-up examinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 28 publications
5
38
1
Order By: Relevance
“…The authors subsequently concluded that END should be reserved for high grade tumours and for those with larger primary tumours. This viewpoint was also supported by other investigators [29, 30]. In the current study, we found that the rate of occult neck metastasis was 27.8% for early stage parotid SCC, while previous authors described a variable occult metastasis rate from 41 to 60% [8].…”
Section: Discussionsupporting
confidence: 90%
“…The authors subsequently concluded that END should be reserved for high grade tumours and for those with larger primary tumours. This viewpoint was also supported by other investigators [29, 30]. In the current study, we found that the rate of occult neck metastasis was 27.8% for early stage parotid SCC, while previous authors described a variable occult metastasis rate from 41 to 60% [8].…”
Section: Discussionsupporting
confidence: 90%
“…In a previous study, Védrine et al (7) reported that differences in OS, DSS, and RFS rates were not statistically significant between primary and secondary MEC groups; only 18 patients were included in their research. Verma et al (27) reviewed 58 cases of secondary MEC in PubMed and reported that the 5-year RFS and OS rates were 95 and 93.4%, respectively, which were slightly better than our outcomes. One possible explanation was that there is much more bias in calculating the survival rates based on case reports worldwide.…”
Section: Figure 2 |contrasting
confidence: 75%
“…However, there were only 18 cases included in the analysis in this study, and this small sample size might greatly decrease its persuasiveness. Recently, Verma et al (27) reviewed 58 cases of secondary salivary MEC. These authors found that the parotid gland was most likely to be involved, that 87.5% of the diseases were low or intermediate grade, and that most of the patients were staged as T1 or T2.…”
Section: Figure 2 |mentioning
confidence: 99%
“…The surgical technique required for SMG preservation is not a concerning matter [ 13 ], and our head and neck department performs nearly 5000 operations every year; thus, our rich experience enables us to face many difficulties [ 24 , 25 , 27 30 ]. The biggest problem involves clearing any possible lymph nodes around the SMG.…”
Section: Discussionmentioning
confidence: 99%